2011
DOI: 10.4103/0974-7788.83183
|View full text |Cite
|
Sign up to set email alerts
|

Blood compatibility studies of Swarna bhasma (gold bhasma), an Ayurvedic drug

Abstract: Swarna bhasma (gold bhasma) preparations are widely utilized as therapeutic agents. However, in vitro biological evaluations of bhasma preparations are needed along with the physicochemical characterization for present day standardization of metallic bhasma preparations to meet the criteria that supports its use. Therefore, an attempt has been made to evaluate the protein adsorption, blood compatibility and complement activation potential of two batches of Swarna bhasma preparation, along with its physicochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…[ 27 ] In blood compatibility study, it was found that Swarna Bhasma contained gold nanoparticles with crystallite size 28–35 nm and was 90% pure gold. [ 28 ] Another study found that colloidal gold uptake in gastrointestinal tract is dependent on particle size that is, smaller particles cross the gastrointestinal tract more readily. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 27 ] In blood compatibility study, it was found that Swarna Bhasma contained gold nanoparticles with crystallite size 28–35 nm and was 90% pure gold. [ 28 ] Another study found that colloidal gold uptake in gastrointestinal tract is dependent on particle size that is, smaller particles cross the gastrointestinal tract more readily. [ 29 ]…”
Section: Discussionmentioning
confidence: 99%
“…The particles of Swarna Bhasma were reported as non-cytotoxic. [ 28 ] In a study of chronic toxicity of Swarnabindu prashana no cytotoxicity was observed. [ 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…[3910] Few recent laboratory studies established the pharmacological effects of gold nanoparticle (main ingredient of SB). Gold-silica nanoshell has been used in Nanoshell-Assisted Photo-Tthermal therapy (NAPT) to kill tumor cells by near Infra Red (IR) light.…”
Section: Discussionmentioning
confidence: 99%
“…Hence a conclusion can be drawn that all the Bhasmas were of the size less than 2 μ in TR. The earlier SEM studies on Swarna Makshika Bhasma - particle size 1-2 μm,[25] Swarna Bhasma -particle size 56-57 nm,[26]669-717 nm,[27] Naga Bhasma -particle size 60 nm[28] and Yashada Bhasma has identifiable fraction of particles in nano size. [29] Particle size distribution of LB - the particle size range of 2.55-40.9 μm was found in Sahastraputi Lauha Bhasma and 5.1-51.6 μm in Satputi Lauha Bhasma .…”
Section: Discussionmentioning
confidence: 99%